Sustainable urban mobility through the perspective of overcompliance - Mehmet Çağrı Köse; Jón Garðar Steingrímsson; Julia Schmid; Roel van Veldhuizen; Dorothea Kübler; Günther Seliger (Procedia CIRP, 2016)
Being at the frontier with regard to sustainable aspects of manufacturing may serve as competitive advantage due to the increasing trend of consumer awareness. In order to adhere to the consequent pressure from external stakeholders such as customers, investors, competitors, interest groups and local municipals, companies voluntarily overcomply with social and environmental norms. This paper explores the incentives for the industry to embrace overcompliance as a strategic means to gain competitive advantage and take the lead in sustainable manufacturing. Examples from recent industrial trends are used to present the relevance of the combination of overcompliance and sustainability in the field of mobility. Studies of the Collaboration Research Center 1026 are presented as additional examples of strategic overcompliance with emission standards in the field of sustainable urban mobility.
Keywords: 330; sustainable manufacturing; voluntary overcompliance; urban mobility